2011
DOI: 10.3171/2011.4.spine10686
|View full text |Cite
|
Sign up to set email alerts
|

Pathological effects and motor response threshold changes following radiofrequency application at various distances from the L-5 nerve root: an experimental study

Abstract: Object Radiofrequency (RF) ablation is a minimally invasive technique often used percutaneously in the treatment of many conditions such as spasticity, pain, and osteoid osteoma. The purpose of this study was to assess the value of motor response threshold (MRT) as an indirect indicator of the RF generator's electrode to nerve distance, and to evaluate the effects of RF at various distances from a nervous structure. Methods<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Based on the results of a previous experimental study in which we determined the safety parameters for the use of radiofrequency in the spine, 8 we found in the current prospective clinical study that radiofrequency is a safe and valid method for the treatment of spinal osteoid osteomas, with excellent long-term results. This condition may thus be managed in a mini-invasive way, avoiding more aggressive neurosurgical treatment.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Based on the results of a previous experimental study in which we determined the safety parameters for the use of radiofrequency in the spine, 8 we found in the current prospective clinical study that radiofrequency is a safe and valid method for the treatment of spinal osteoid osteomas, with excellent long-term results. This condition may thus be managed in a mini-invasive way, avoiding more aggressive neurosurgical treatment.…”
Section: Discussionmentioning
confidence: 96%
“…When no motor response is observed until 2.5 V, the tip of the electrode is considered to be at a safe distance of at least 5 mm of the adjacent nervous elements, based on the experimental study published by our team. 8 After the motor response threshold test was performed, the electrode was connected to a radiofrequency generator (Neuro N50, [IEC 601-1, FDA, UL-listed, Med.GB]), which delivered a radiofrequency of 500 kHz with a controlled temperature of 82°C. This temperature was maintained for 4 minutes.…”
Section: Operative Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…High temperature could induce cellular apoptosis and necrosis. e damage caused at high temperatures of 95°C could evidently damage the neurons and nerve fibers [19,20]. Active damaging of the nerves for the treatment of some diseases has been highly accepted by the patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that when treating osteoid osteoma, 90°C of heat should be applied for approximately five minutes for the necrosis of the entire tumor [9,13]. When this energy is applied to the tumor, a 2 to 5mm margin from the nerve has been postulated to be the safety threshold [14,15]. Although epidural vein plexus and cerebrospinal fluid may reduce the possible side effects, when the tumor is within 5mm of the spinal canal, it is prudent to undergo an open resection of the nidus.…”
Section: Discussionmentioning
confidence: 99%